Fikrah Dakwah T.M. Hasbi Ash-Shiddieqy dalam Tafsirnya - Amir, Ahmad Nabil (Sekolah Tinggi Ilmu Al-Quran Isy Karima Karanganyar, 2024)
The paper discusses T.M. Hasbi ash-Shiddieqy’s contextual approaches in his Qur’anic exegesis, kitab Tafsir al-Quran al-Majid or Tafsir an-Nur. It brings to light the principal ideas and framework of dakwah as set forth in his Tafsir and analysed the essence and practical ways of dakwah as alluded to in his commentary of verses and themes of dakwah in the Qur’an. It focused on his two phenomenal works, Tafsir al-Quran al-Majid and Tafsir al-Bayan that substantively displayed his unique ideas in formulating the concept and approaches of dakwah and developed significant understanding of the interpretation of ayat al-dakwah and its implication in enhancing spirituality and religiosity of Muslim in Indonesia. The structure of research is framed on qualitative approaches in the type of documentary survey of related literature. The findings suggest that its interpretation emphasizes the significant aspirations for renewal in legal thought and preaching, using the power of ijtihad. Its perspective relates to the ideology and idealism of preaching, along with efforts to outline a modern approach within the context of preaching in the contemporary era.